Targeting DNA Damage Response and Replication Stress in Pancreatic Cancer - Dreyer, Stephan B.; Upstill-Goddard, Rosie; Paulus-Hock, Viola; Paris, Clara; Lampraki, Eirini Maria; Dray, Eloise; Serrels, Bryan; Caligiuri, Giuseppina; Rebus, Selma; Plenker, Dennis; Galluzzo, Zachary; Brunton, Holly; et al. (Gastroenterology, 2021)
Background & Aims: Continuing recalcitrance to therapy cements pancreatic cancer (PC) as the most lethal malignancy, which is set to become the second leading cause of cancer death in our society. The study aim was to investigate the association between DNA damage response (DDR), replication stress, and novel therapeutic response in PC to develop a biomarker-driven therapeutic strategy targeting DDR and replication stress in PC. Methods: We interrogated the transcriptome, genome, proteome, and functional characteristics of 61 novel PC patient–derived cell lines to define novel therapeutic strategies targeting DDR and replication stress. Validation was done in patient-derived xenografts and human PC organoids. Results: Patient-derived cell lines faithfully recapitulate the epithelial component of pancreatic tumors, including previously described molecular subtypes. Biomarkers of DDR deficiency, including a novel signature of homologous recombination deficiency, cosegregates with response to platinum (P <.001) and PARP inhibitor therapy (P <.001) in vitro and in vivo. We generated a novel signature of replication stress that predicts response to ATR (P <.018) and WEE1 inhibitor (P <.029) treatment in both cell lines and human PC organoids. Replication stress was enriched in the squamous subtype of PC (P <.001) but was not associated with DDR deficiency. Conclusions: Replication stress and DDR deficiency are independent of each other, creating opportunities for therapy in DDR-proficient PC and after platinum therapy.
CRIS-Team Scopus Importer:2020-12-25
Keywords: DNA Damage Response; Pancreatic Cancer; Personalized Medicine; Replication Stress